2001
DOI: 10.1111/j.1151-2916.2001.tb00636.x
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Carbide Films by Laser Pyrolysis of Polycarbosilane

Abstract: Thin films of polycarbosilane were deposited on Si and SiO 2 substrates. Instead of conventional oven annealing (high temperatures, inert atmosphere), laser pyrolysis was used to achieve the polymer-to-ceramic conversion. In some conditions, especially when laser radiation absorption was enhanced by depositing a carbon layer on the surface of as-deposited films or by embedding graphite particles, this processing method yielded SiC ceramic coatings, without damaging the substrate. Processing in air or low vacuu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 7 publications
1
25
0
Order By: Relevance
“…A thin protective coating of SiC has found to be very effective in harsh environments [7], although there are reports that Si structures fabricated by deep reactive ion etching (DRIE) do not perform well in erosive environments [8], since SiC is a semiconductor with wide bandgap so it offers a promising coating material on silicon for MEMS application. Chemical vapor deposition (CVD), physical vapor deposition (PVD), atomic layer epitaxy, molecular beam epitaxy, sputtering, or laser ablation have been successfully employed to deposit single and polycrystalline forms of SiC thin films on substrate [9][10][11][12]. Each technique has its own merits and limitations.…”
Section: Introductionmentioning
confidence: 99%
“…A thin protective coating of SiC has found to be very effective in harsh environments [7], although there are reports that Si structures fabricated by deep reactive ion etching (DRIE) do not perform well in erosive environments [8], since SiC is a semiconductor with wide bandgap so it offers a promising coating material on silicon for MEMS application. Chemical vapor deposition (CVD), physical vapor deposition (PVD), atomic layer epitaxy, molecular beam epitaxy, sputtering, or laser ablation have been successfully employed to deposit single and polycrystalline forms of SiC thin films on substrate [9][10][11][12]. Each technique has its own merits and limitations.…”
Section: Introductionmentioning
confidence: 99%
“…The spectra showed that the adsorption peak of Si-H in the film cured with oxidation was lower than that with irradiation. The presence of Si-H, Si-CH 2 -Si, Si-O-Si, and Si-CH 3 modes in their spectra, together with the measured stoichiometric ratios, suggested the formation of -[SiH(CH 3 …”
Section: Compositional and Structural Analysismentioning
confidence: 91%
“…[1][2][3] SiC films could also be used as a material for the next generation of high-power, high-temperature electronic and optoelectronic devices. 4 Amorphous and polycrystalline ␤-SiC films had attracted much attention for the applications such as hard protective coatings, semiconductor, structural materials for power microelectromechanical systems (MEMS) in harsh environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The heating rate affects the ceramic yield and composition [34]. Heating rate, dwelling temperature and time influence the composition and microstructure of the matrix, as they affect the extent of crystallization, carbothermal reduction reactions and filler reactions occurring in the material.…”
Section: Composite Processing and Characterizationmentioning
confidence: 99%